Peluang Investasi Rumah Kost di Tengah Berdirinya Binus Square - Dyah Budiastuti; Andri Prabowo (Bina Nusantara University, 2010)
Boarding house around Binus University campus which is the informal sector continue flourishing and developing in line with the development of Binus University. Investors continue to invest in this business with a capitalization of billions of rupiah. With the increasing demand from year to year and the utility room that is always high, in July 2010 this boarding house business had to deal with Binus Square, a new business unit of Binus which is a special exclusive residential for Binus University students with a capacity of 2500 people.This research aims to find out are there still investment opportunities of boarding house amid the establishment of Binus Square through the creation of competitive advantage. Data are retrieved through questionnaires which are circulated to residents of boarding houses that served Binus Access and analyzed by using descriptive statistics.The result showed that there are still opportunities to open up boarding houses around Binus University with a focus on improving facilities and services that lead to private services.